The effect of six weeks CoBAgi training on coordination, dynamic balance & agility of adolescent handball players - Mohamad Hasif B. Mohamad Puzi; Lee A. Choo (IP Iermakov S.S., 2021)
Background and Study Aim. The aim of this study is to investigate the effects CoBAgi Training which apply neuromuscular training, sport specific movements that couple with perturbation variation on coordination, dynamic balance and agility among adolescent handball players. Material and Methods. Quantitative randomized controlled trials quasi-experimental design with pretest and posttest evaluation used for this study. A total of 30 adolescent handball players (aged: 14.00 ± 0.83 years) were recruited as participants. Purposive sampling methods were used for these purposes. The participants were randomly assigned into two groups i.e. control group (CG: n=15) and experimental group (EG: n=15). EG undergone six weeks CoBAgi training while CG followed their usual training routine with supervision of the researcher, there times a week for 6 weeks. In order to measure the effect of these training on coordination, dynamic balance and agility, participants have performed Carioca Test, Star Excursion Balance Test (SEBT) and L-Run Test during pre-training and post-training session. The data were analyzed through Independent Samples t-test with p<0.05 "Statistical Package for the Social Sciences" (SPSS) program. Result. After completed the six weeks training duration, there were significant difference identified in coordination (t=-2.290, P=0.030*), dynamic balance (t= 4.802, P=0.000*) and agility (t=-3.202, P= 0.003*) between EG and CG. Conclusion. Therefore, this study revealed that CoBAgi training could improve abilities performance of coordination, dynamic balance and agility, and this suggesting that CoBAgi training may be use as rehabilitation and pre-rehabilitation training strategies in order for injury prevention plan as well as improve sports performance especially among the adolescent handball players.